Analisis Resepsi Audiens terhadap Serial Edutainment Academy of Champions yang Ditayangkan pada Channel YouTube Ruangguru - Azwa Mulya Putri; Ainun Ni’matu Rohmah; Nurliah; Harry Isra Muhammad (Jurnal Ragam Pengabdian, 2026)
The establishment of the online learning platform Ruangguru was based on the phenomenon of digital transformation, which creates effectiveness and efficiency in the learning process. As a way to increase public interest, Ruangguru created a new strategy by producing an edutainment program called Academy of Champions. This study aims to analyze how the audience perceives the content of the Academy of Champions series aired on Ruangguru's YouTube channel. Using a qualitative approach with Stuart Hall's reception analysis method, this study classifies audience responses into three categories of meaning: dominant-hegemonic position, negotiated position, and oppositional position. Data was collected through in-depth interviews with research subjects, who were students from SMA Negeri 10 Samarinda. The results of the analysis show that most informants were in the dominant-hegemonic position, whose assessments were in line with the main discourse of Academy of Champions because the series successfully presented representations of outstanding students who could be a source of inspiration and motivation for learning. Meanwhile, informants in the negotiated position needed to adjust the meaning based on their interests and learning style preferences. This study shows that the interpretation of the show's messages is diverse and influenced by personal experiences, motivation, learning preferences, and interest in entertainment.